Rare diagnosis of Ebstein anomaly in an adult patient in Northern Rio de Janeiro - Britto, Rogerio Muylaert de Carvalho; Liborio Neto, Adail Orrith; Ramos, Otávio Defanti; Defanti, Mirele da Silva Cruz (Clinical and Biomedical Research, 2021)
Ebstein anomaly is the fourth most frequent cyanotic heart disease in the neonatal period, and its clinical course is slow compared to other diseases, which in turn results in late diagnosis of this condition. We present a case of a 37-year-old man who complained of palpitation for about 5 years, twice a week, at rest, with prolonged duration and low systemic output. Auscultation revealed irregular heart rhythm characterized by extrasystoles with a tricuspid systolic murmur grade 5+/6 and worsening on inspiration. Clinical spectrum is variable and depends on the severity of defects and associated anatomical changes. In patients who have reached adulthood, symptoms usually present as progressive cyanosis, exercise intolerance, right heart failure, and arrhythmias. In Brazil, identification of this congenital disease usually occurs in a more adult phase, affecting the prognosis and survival of patients.